Influences of weight and thickness on cooking time required for various mechanically tenderized beef steaks to reach minimum safe internal temperature without resting. (August 2019) - Saha, Joyjit; Jaroni, Divya; Nelson, Jacob; Willoughby, Chuck; McDaniel, Conner; Jadeja, Ravi
Abstract: This study was conducted to determine safe cooking times for mechanically tenderized beef steaks prepared from the round, loin, rib, and chuck. The subprimals were needle tenderized and fabricated to prepare a total of 180 steak cuts with varying weights and thicknesses. Steaks were then vacuum packaged and stored at refrigerated temperature until cooked. The dimensions and weight of the steaks were measured pre- and post-cooking. Samples were cooked on a flat-top grill until they reached an internal temperature of 71.1 °C. During cooking, a thermocouple recording device recorded the steak center temperature every 10 s. It was observed that the time required for the steak to reach 71.1 °C significantly influenced by the thickness and type of subprimals of steak. The average cooking yield of steak was 75.66%, while the safe cooking time ranged from 2.22 to 36.66 min. This study could provide valuable information about the effects of weight, thickness and muscle type on the cooking time required for mechanically tenderized beef steaks to reach a minimum safe cooking temperature, without a resting period. Highlights: Safe cooking times determined for mechanically tenderized beef steak cuts. Safe cooking time varied with subprimals and thickness of cuts. Cooking yield was unaffected by mechanical tenderization.